The Study of Relationship Between Managers Personality Types with Their Efficacy (Case Study of Islamic Azad University of Qaemshahr) - et. al., Mojtaba Tabari, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The present study has been don to examine the relationship between managers personality types whit their efficacy in Islamic Azad Univarsity of Qaemshahr. the main hypothesis is as follow there is a meaningful relation ship between managers personality types and their eficiacy. the statistical universe of this study is divided into two groups of manaders and employees that according to the repart of administration unit 20 persons are managers and 210 persons are employees that 136 person were chosen asa sample in simple random manner amongemployees. Among personality models, pour styles of yong eight styles was chosen that consist extroverted, sensational, logical and disciplined. Efficacy index is also b ased on the elements of wikipeid encyclopedia. In formation collecting tools in this researcal are two guestionnaire as follow: Employees. Reseach results were confirmed the main hypothesis namely the relationship among special kinds of persomality styles with management efficiacy. In lateral results we found that the most efficacious personality style is sensual style in mangers.